MENINGKATKAN PROFESIONALISME GURU MENGAJAR MELALUI PENERAPAN PENILAIAN KINERJA GURU DI SMP NEGERI 5 SINGINGI KABUPATEN KUANTAN SINGINGI - Andriyuan Andriyuan (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
The teacher is a professional educator so that has the task, function, and important role in educating the life of anation. The requirements to be referred to as professional educators, among others, have skills based onconcepts and theories of science, based on philosophical, psychological, and sociological. A teacher must alsohave adequate competence, while the competence includes professional, pedagogical, social, and personalcompetence. In this School Action Research, attempts were made in an effort to Improve Professionalism TeachTeachers were Raised Through Application of Teacher Performance Appraisal at State Junior High School 5Singingi Kuantan Singingi Regency. This research understands qualitative approach because it is moreappropriate to identify teacher performance appraisal in improving teacher teaching professionalism. Theresults of this research The Efforts of the First High School Principal of the 5 Singingi Affirm the improvementof professionalism of teachers that have been done through: 1) Guidance to teachers in preparing lessonplans.2) Monitoring teachers in implementing learning.3) Monitoring the course of educational activities .d.Checking the state and integrity of State Junior High School facilities as a supporter of student achievement .. 4)Evaluating through briefings and meetings of educational programs in an effort to improve the professionalismof teaching teachers in class.